PENERAPAN RELAKSASI AUTOGENIK PADA PASIEN DIABETES MELITUS TIPE 2 DENGAN KETIDAKSTABILAN KADAR GLUKOSA DARAH - Mustofa, Adi; Sumarni, Tri; Siwi, Adiratna Sekar (Maternity and Neonatal : Jurnal Kebidanan, 2025)
Instability of blood glucose levels is one of the signs that appears in patients with type 2 diabetes mellitus. The incidence of type 2 diabetes mellitus is increasing from year to year. This has an impact on uncontrolled blood glucose levels in type 2 diabetes mellitus patients. To describe care for type 2 diabetes mellitus patients with the problem of unstable blood glucose levels by providing autogenic relaxation. This scientific writing method uses a case study with a descriptive design. The respondent in this paper is 1 patient with a medical diagnosis of DM pedis dextra abscess in the Dahlia room at RSUD Dr. R. Goeteng Taroenadibrata Purbalingga. Nursing care is carried out for 4 days of treatment. The results showed that after being given treatment, especially autogenic relaxation, for 4 days, patients with unstable blood glucose levels experienced a decrease in blood glucose levels. After treatment for 4 days, providing autogenic relaxation can reduce blood glucose levels in patients with type 2 diabetes mellitus. Autogenic relaxation still needs to be given to patients with type 2 diabetes mellitus to maintain and reduce blood glucose levels independently